2019
DOI: 10.1177/1179556519841876
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar Nerve Injuries Post Closed Forearm Fractures in Paediatric Population: A Review of the Literature

Abstract: Ulnar nerve injury as a result of closed forearm fractures in children is a rare but disastrous complication, affecting significantly the function of the upper extremity. The management of these injuries is still controversial in the literature. This is a review of small case series and case reports, in which an algorithm of treatment is proposed. A brief description of a relative case, which was treated successfully in our department, is presented as well. This case motivated the authors to perform this study. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…This includes an unacceptable or lost reduction of the limb, open fractures, fractures in patients with less than two years left to complete growth, neurovascular compromise, and certain pathological fractures [4]. Ulnar nerve palsy can happen as a result of several causes: direct nerve contusion, scar tissue or bone entrapment, or partial nerve laceration [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes an unacceptable or lost reduction of the limb, open fractures, fractures in patients with less than two years left to complete growth, neurovascular compromise, and certain pathological fractures [4]. Ulnar nerve palsy can happen as a result of several causes: direct nerve contusion, scar tissue or bone entrapment, or partial nerve laceration [3].…”
Section: Discussionmentioning
confidence: 99%
“…It can be detected at various stages, sometimes immediately (with the injury), postmanipulation, or even at a later date. In cases of worsening neuropraxia [3], MRI can be used to determine the status of the nerve in a case of worsening neuropraxia [3]. Although both-bone forearm fractures are typically managed conservatively [4], Stavrakakis et al [3] concluded that surgical exploration of the nerve should be performed when palsy is accredited to manual manipulation or when neuropraxia worsens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment can vary from conservative observation of the neuropraxia to nerve exploration and repair for nerve transection or laceration. Stavrakakis et al [ 12 ] recommended nerve exploration for post manipulation nerve palsy, worsening nerve injuries, and those not showing any improvement after 20 weeks of injury. Anatomical fracture fixation is essential for favorable functional outcome after the injury [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Популярными являются нейровенные трансплантаты икроножного, локтевого и поверхностной веточки лучевого нервов. При одновременном застарелом повреждении срединного и локтевого нервов васкуляризированный трансплантат локтевого нерва считается оптимальным вариантом для реконструкции срединного нерва [4,38].…”
Section: о б з о р ы л и т е р а т у р ыunclassified